Claw statistics and conformation in relation to age, lactation, body weight, heart girth, rump width and lesions score in dairy cattle and buffaloes - RANDHAWA, SWARAN S; DUA, K; GREWAL, R S; JAVED, M; MALHOTRA, P (The Indian Journal of Animal Sciences, 2014)
Claw measurement is necessary to evaluate the effect of claw size on the lameness. A study was conducted on 54 crossbred cattle and 82 Murrah buffaloes maintained under similar feeding and management practices at university dairy farm. The animals were first evaluated for lameness on a five point scale. Each animal was then restrained in a lameness chute and claw measurements, viz. foot angle, claw length, length of the dorsal border, coronary band, abaxial groove and base were measured. Besides these, animal age, lactation number and body weight, heart girth and rump width were recorded. Claw volume (cm3) was calculated using Scott et al. (1999) formula. Multiple linear regression analysis of the data revealed that claw volume of the cattle increased with increasing age, lactation number, heart girth and rump width but not with the increasing body weight. In buffaloes, claw volume increased as the age, lactation number, rump width, heart girth and body weight of the animal increased. The cumulative effect of all the independent variables was more evident in cattle (R2 = 0.67) as compared to buffaloes (R2 = 0.42). Claw volume/body weight ratio was significantly more in buffaloes, whereas lameness score was more in cattle as compared to buffaloes. A significant positive correlation between lameness score and claw volume/body weight ratio was observed in cattle (r=0.36). Total lesion score showed a significant negative correlation with claw volume/ body weight ratio indicating buffaloes with more claw volume per unit body weight have less lesion score. Buffaloes were having smaller foot angles therefore having more claw lengths and lengths of the dorsal border as compared to cows.